"m^3-7m =0;\\ m(m^2-7)=0\\\\\n\\therefore m_1=0,m_2=\\sqrt{7}\\\\\nC.F=\\phi_1 (y+m_1 \\cdot x)+\\phi_2 (y+m_2 \\cdot x)+x\\ \\phi_3 (y+m_2 \\cdot x)\\\\\nC.F=\\phi_1 (y+0 \\cdot x)+\\phi_2 (y+(\\sqrt{7}) \\cdot x)+x\\ \\phi_3 (y+(\\sqrt{7}) \\cdot x)\\\\"
"P.I=\\frac{sin(x+2y) + e^{2x}+y}{D\u00b3 \u2013 7DD'\u00b2 \u20136D'\u00b3}\\\\\nF(D,D')=D\u00b3 \u2013 7DD'\u00b2 \u20136D'\u00b3;\\ Where\\ a=1, b=2\\\\\nf(a,b)=(1,2)=1^3-7(1)(2)^2-6(2)^3=1-7(4)-6(8)\\\\\n\\implies-75 \\ne0\\\\"
"P.I=\\frac{1}{f(a,b)}\\intop \\intop sin\\ v\\ \\delta v \\delta v + \\intop \\intop (e^{2x}+y)\\ \\delta y \\delta x \\\\\n\\implies \\frac11\\intop \\intop -cos\\ v\\ \\delta v \\delta v \\\\\n\\implies 1\\intop \\intop -sin\\ v\\ \\delta v =cot\\ v= cot(x+2y)\\\\\nand\\\\\n\\implies \\intop \\intop (e^{2x}+y)\\ \\delta y \\delta x =\\intop e^{2x}+y)\\ \\delta y = e^{2x}y+\\frac{y^2}{2}\\\\\n\\implies \\frac{y^2}{2}x+y \\frac12 e^{2x}\\\\\nP.I =cot(x+2y)+\\frac{y^2}{2}x+y \\frac12 e^{2x}\\\\"
General Solution
"C.F+P.I= \\phi_1 (y+0 \\cdot x)+\\phi_2 (y+(\\sqrt{7}) \\cdot x)+x\\ \\phi_3 (y+(\\sqrt{7}) \\cdot x)+cot(x+2y)+\\frac{y^2}{2}x+y \\frac12 e^{2x}\\\\"
Comments
Leave a comment